Social Capital as a Predicting Indicator to Measure the Psychological Health Impacts of COVID-19 Pandemic on Urban Societies in Pakistan. - Saleha Ansari; Dr Sadaf Konain Ansari (International Journal of Urban Design and Development, 2024)
The COVID-19 pandemic has forced people to adapt to massive changes in their lifestyles; from health to work and how they interact with everyone nearby they know. This study aims to investigate the psychological wellbeing-impacts of COVID-19 on social capital in Pakistan. Social capital means the social and cultural coherence (as a predicting indicator) in the society. This was a survey based study conducted in 5 major cities (Islamabad, Rawalpindi, Lahore, Peshawar and Karachi) of Pakistan during the period of January to November 2023 (11 months). The dimensions through which social capital is being studied includes; perceived safety and trust, participation in network development, personal empowerment, attitude towards government and relations within workplace. These dimensions were studied through a number of indicators which were a part of the survey. Total sample size was 277 with aged between 20-to-30-years. Though there isn’t much literature present on COVID-19, since the pandemic was only 4-years old, the study employed published research to strengthen its case. The data obtained were sent to SPSS statistics to explore and examine the psychological impact of the pandemic on various characteristics of social capital with chi-square value less than 0.01 was significant.
Keywords: COVID-19 pandemic; Cultural and heritage damage; Economic growth; Ecotourism, History, hospitality, Sustainable; Social capital